The participation of indigenous women in the democracy of Ecuador - Herrera Acosta, Carlos Ernesto (2021)
Women in general and indigenous women have been excluded from various activities of the human being, adducing macho and patriarchal theories that have discriminated and minimized the ability of women to carry out tasks that throughout history have shown to do better than men. men, this perception has made a significant difference between men and women; The fight of women for the respect of their rights, for equality and equity in Ecuador, originates precisely in the rural sector, their voice of protest and their perseverance have been a fundamental pillar in the reach of collective rights of the peoples and indigenous nationalities. The article describes some aspects related to the evolution of the participation of indigenous women in the democratic and political life of Ecuador; To achieve this purpose, an analysis of indigenous women, democracy and citizen participation is carried out, taking as an approach the ancestral and mestizo worldview, to conclude by describing the role of the aboriginal warmi in the political parties and movements of Ecuador.